Preservice Training of Science Teachers: Using the Views of Non-Science Specialists - David Palmer (Networks: An Online Journal for Teacher Research, 1999)
There is considerable evidence that many high school students are losing interest in science (Yager and Lutz, 1995). I am involved in the training of science teachers, and I wanted to develop a student-centred approach which would present this issue to future science teachers. I believe it is not only important for them to be aware of this problem, but also to be aware of the classroom practices which may exacerbate it, so that these practices can be avoided. This article describes a technique in which non-science college students were used to present these issues to preservice science teachers. It was carried out at the beginning of a one semester subject in science teaching methods.